Medication Errors Associated with the Use of Levofloxacin: An Analysis of the National Database of Spontaneous Reports - I. L. Asetskaya; S. K. Zyryanov; K. I. Samsonova; O. I. Butranova; E. N. Terekhina; V. A. Polivanov (Безопасность и риск фармакотерапии, 2025)
INTRODUCTION. Newly identified risks associated with the use of fluoroquinolones and the spread of antimicrobial resistance make the identification and analysis of medication errors (MEs) in prescribing fluoroquinolones especially important for providing rational antibiotic therapy. Fluoroquinolones that are most commonly used in real-world clinical settings include levofloxacin.AIM. This study aimed to examine the pattern of MEs associated with fluoroquinolones, exemplified by levofloxacin, through an analysis of spontaneous reports (SRs) submitted to the Russian pharmacovigilance database.MATERIALS AND METHODS. The authors retrospectively analysed the SRs of adverse drug reactions (ADRs) submitted to the Russian pharmacovigilance database between 1 April 2019 and 28 February 2023. According to the selected inclusion criteria, the study focused on the SRs that specified levofloxacin as a suspect medicinal product and described ADRs that took place in the Russian Federation. ME identification used summaries of product characteristics for levofloxacin approved in Russia, official clinical guidelines, and the antimicrobial stewardship guidelines Strategy for the Control of Antimicrobial Therapy (SCAT).RESULTS. The analysis included 950 SRs. MEs were identified in 307 (32.3%) of these SRs, and the total number of MEs was 332. MEs associated with the selection of the medicinal product included prescribing levofloxacin to patients without an indication for antibacterial therapy (38.9%, n=129, with 76.0% of cases being viral infections), incorrect selection of levofloxacin as a first-line antibacterial agent (18.1%, n=60), and irrational and excessive prescribing of levofloxacin in combination with other antibacterial agents (15.4%, n=51). Less frequently identified MEs were related to inappropriate dosing (13.0%, n=43), levofloxacin use in patients with contraindications (8.7%, n=29), and incorrect selection of the route of administration (3.9%, n=13) and the dosage form (2.1%, n=7).CONCLUSIONS. According to the results of this study, the practice of prescribing antibacterial agents for viral infections persists despite strong evidence of ineffectiveness in such cases. Antibacterial agents can be used effectively and safely only if prescribed for approved indications, administered at recommended doses, and delivered via specified routes of administration. The overuse of antibiotics may have negative sequelae not only for the health of an individual patient but for the health of the general population because of the increased risk of antimicrobial resistance. Therefore, there is a need to develop measures to limit the excessive use of antibiotics.